Problem Solving: A Collaborative Learning Approach Using Computer Network - Newbury, Angela; Whitworth, David (Proceedings of the International Conference on Networked Learning, 1998)
An aim in any award is to enhance the communication and transferable skills of the learner and promote problem solving activities involving the content of the modules that make up that award. The design information network (EDNET) has been set up to enable learners to exercise their skills using the new medium of computer networks. Microsoft products are used to create information in electronic form which can then be accessed through a World Wide Web browser.